A New Method for Measuring the Thermal Insulation Properties of Fibrous Silica Aerogel Composite. (2015) - Mazraeh-shahi, Z. Talebi; Shoushtari, A. Mousavi; Bahramian, A.R.
Abstract: In this work, the thermal diffusivity and thermal conductivity of nonwoven fabric and silica aerogel/nonwoven fabric composite was determined by a new method for the investigation and comparing the thermal insulation properties of them. The thermal diffusivity of the neat nonwoven fabric and its silica aerogel composite was calculated from the temperature distributions curves and the numerical solution of the heat transfer equations. The temperature distributions curve was obtained using Marsh cooling method in which the cooling rate of a fluid such as water or oil inside a hot body wrapped with fibrous sample could be measured. The results showed that the presence of silica aerogel in the matrix of nonwoven fabric led to significant decrease in the thermal diffusivity of the composite (1.3×10 -7 m 2 /s) compared to the neat nonwoven fabric (2.6×10 -7 m 2 /s).